Meningkatkan Kemampuan Membaca Meningkatkan Kemampuan Membaca Menggunakan Metode Struktural Analitik Sintetik untuk Siswa Kelas 1 Sekolah Dasar - Riyasih Asih; Muhamad Sofian Hadi (CENDEKIAWAN, 2025)
This study aims to enhance the early reading and writing skills of first-grade students at SD Muhammadiyah Aimas through the Structural Analytic Synthetic (SAS) method. The motivation behind this research stems from the observation that students’ early reading skills were still below the Minimum Competency Criterion (KKM). This research is classified as Classroom Action Research (CAR), involving 20 students from grade 1 at SD Muhammadiyah Aimas as subjects. Data collection techniques included observation sheets, reading ability tests, and interviews. The results indicated that the learning implementation aspect improved from an average of 66% in Cycle I to 80% in Cycle II, categorizing it as "very good." Student participation also increased from 66% in Cycle I to 86% in Cycle II, again falling under the "very good" category. The average scores for reading and writing abilities saw a significant increase from 74.57 in Cycle I to 87.5 in Cycle II. It can be concluded that the first-grade students at SD Muhammadiyah Aimas successfully improved their reading and writing skills through the SAS method. In relation to the school’s KKM for the Indonesian language subject, students are considered successful if they achieve 80%, equating to a score of 67 or higher. Therefore, the findings affirm that the SAS method effectively enhances the early reading and writing capabilities of students in grade IA at SD Muhammadiyah Aimas.